Preparation method of coating slurry, silver-carbon negative plate, preparation method of silver-carbon negative plate and solid-state battery

By controlling the degree of agglomeration of silver particles in the silver-carbon anode sheet, uniform dispersion of silver and carbon particles is achieved, solving the problem of lithium dendrite formation in the silver-carbon anode sheet and improving the safety and electrical performance of the battery.

CN120914202APending Publication Date: 2025-11-07CHINA AVIATION LITHIUM BATTERY RES INST CO LTD +1

Patent Information

Application Number
CN202511146570.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-15
Publication Date
2025-11-07

AI Technical Summary

Technical Problem

In the existing silver-carbon anode sheet manufacturing process, the silver particles are not evenly dispersed, which leads to the formation of lithium dendrites, affecting the safety and electrical performance of the battery.

Method used

By controlling the degree of agglomeration of silver particles in the silver-carbon anode sheet, the silver and carbon particles are evenly dispersed, increasing the attachment sites and space of silver particles on carbon particles. A specific mixing and stirring method is used to prepare the coating slurry to ensure the uniform distribution of silver particles in carbon particles.

Benefits of technology

It improves the safety and electrical performance of the battery, avoids the formation of lithium dendrites, and enhances the battery's stability and electrochemical lifespan.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120914202A_ABST
    Figure CN120914202A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly relates to a preparation method of coating slurry, a silver-carbon negative electrode plate, a preparation method of the silver-carbon negative electrode plate and a solid-state battery. Compared with the prior art, by controlling the agglomeration degree of the silver material in the negative electrode active coating, silver and carbon particles can be uniformly dispersed, and on the basis of avoiding the generation of lithium dendrites, attachment sites and spaces of the silver particles on the carbon particles are increased, so that the safety performance and the electrical performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of batteries, and particularly relates to a preparation method of a coating slurry, a silver-carbon negative electrode sheet and a preparation method thereof, and a solid-state battery. BACKGROUND

[0002] The full-solid-state lithium ion battery using metal lithium as a negative electrode is far superior to the traditional lithium ion battery in terms of capacity and energy density. However, uncontrolled dendrite growth of the lithium negative electrode and low coulomb efficiency seriously restrict the practical development of the full-solid-state lithium ion battery.

[0003] Studies have shown that the Ag-C nano composite electrode replacing metal lithium as a battery negative electrode has high specific capacity and stable coulomb efficiency, avoids excessive use of lithium metal, and can effectively regulate the deposition-stripping process of the metal lithium, thereby giving the full-solid-state lithium ion battery a longer electrochemical life.

[0004] However, the preparation of the silver-carbon negative electrode is to coat the silver-carbon slurry on the current collector to form, which is easy to cause uneven deposition of lithium ions and easy to cause lithium dendrites after being coated into a sheet, which will affect the safety and electrical performance of the battery. SUMMARY

[0005] Therefore, the technical problem to be solved by the present application is to provide a silver-carbon negative electrode sheet and a preparation method thereof, and a solid-state battery, wherein the silver particles in the silver-carbon negative electrode sheet are uniformly dispersed and have a small porosity.

[0006] The present application provides a silver-carbon negative electrode sheet, which comprises a negative electrode current collector and a negative electrode active coating attached to at least one surface of the negative electrode current collector; the negative electrode active coating comprises silver particles and carbon particles; in a scanning electron microscope image at a magnification of 100KX, the area of first particles with a particle diameter greater than or equal to 200 nm is S0, and the area of the silver-carbon negative electrode sheet in the scanning electron microscope image at a magnification of 100KX is S, S0 / S≤39.8%.

[0007] Preferably, S0 / S is 2.5% to 25%.

[0008] Preferably, S0 is 0.022 to 0.35 μm 2 .

[0009] Preferably, the number of the first particles under the area S is 1 to 5.

[0010] And / or, the maximum diameter of the first particles is less than or equal to 500 nm.

[0011] Preferably, the silver particles are selected from one or more of spherical silver particles, flaky silver particles, dendritic silver particles and cubic silver particles.

[0012] And / or, the carbon particles are selected from one or more of carbon black, carbon tubes and carbon fibers;

[0013] And / or, the silver particles have a mass of 10% to 40% of the mass of the carbon particles;

[0014] And / or, the negative current collector is selected from copper foil, carbon-coated copper foil, nickel-plated copper foil or stainless steel foil.

[0015] The present application also provides a preparation method of the above silver-carbon negative electrode sheet, comprising the following steps:

[0016] S1) mixing silver particles, binder powder and additives to obtain a first mixture;

[0017] S2) adding a solvent to the first mixture and stirring to obtain a second mixture; the solid content of the second mixture is 20% to 50%;

[0018] S3) adding carbon particles and a solvent to the second mixture in batches in a circulation manner to adjust the viscosity of the slurry to 2500 to 5500 mPa / s and the solid content to 10% to 45% to obtain a coating slurry;

[0019] S4) transferring the coating slurry to the surface of the current collector and drying to obtain a silver-carbon negative electrode sheet;

[0020] Alternatively, comprising the following steps:

[0021] A1) mixing a binder powder and a solvent to obtain a binder glue, and dividing the binder glue into a first binder glue and a second binder glue;

[0022] A2) mixing the first binder glue, silver particles, additives and a solvent and stirring to obtain a third mixture; the solid content of the third mixture is 20% to 50%;

[0023] A3) adding carbon particles and a solvent to the third mixture in batches in a circulation manner, then adding the second binder glue and stirring to adjust the viscosity of the slurry to 2500 to 5500 mPa / s and the solid content to 10% to 45% to obtain a coating slurry;

[0024] A4) transferring the coating slurry to the surface of the current collector and drying to obtain a silver-carbon negative electrode sheet.

[0025] Preferably, the rotation speed of the mixing in step S1) is 10 to 40 rpm; the linear speed of the mixing is 5 to 10 m / s; and the mixing time is 5 to 20 min;

[0026] And / or, the solvent in step S2 is added in batches, specifically: a part of the solvent is added in the first mixture to a solid content of 30% to 60% for first mixing and stirring, and the solvent is continuously added to a solid content of 20% to 50% for second mixing and stirring, to obtain a second mixture; the rotating speed of the first mixing and stirring and the second mixing and stirring is independently 30 rpm to 80 rpm; the time of the first mixing and stirring and the second mixing and stirring is independently 30 min to 60 min;

[0027] In step A2, the first binder glue, silver particles and additives are mixed to control the solid content to be 30% to 60% under a first preset condition, and then the solvent is added to the solid content to be 20% to 50% under a second preset condition, to obtain a third mixture; the rotating speed of the first preset condition mixing and stirring and the second preset condition mixing and stirring is independently 30 rpm to 80 rpm; the time of the first preset condition mixing and stirring and the second preset condition mixing and stirring is independently 30 min to 60 min.

[0028] Preferably, the number of times of cyclic batch addition in step S3 is greater than or equal to 3; the rotating speed of stirring after each batch of carbon particles and solvent is added is independently 10 rpm to 40 rpm, the linear speed of stirring is independently 5 m / s to 10 m / s, and the time of stirring is independently 1 min to 10 min;

[0029] The rotating speed of mixing after the last batch of carbon particles and solvent is added in step S3 is 30 rpm to 80 rpm; the linear speed of mixing is 18 m / s to 23 m / s, and the time of mixing is 60 min to 150 min;

[0030] The number of times of cyclic batch addition in step A3 is greater than or equal to 3; the rotating speed of stirring after each batch of carbon particles and solvent is added is independently 10 rpm to 40 rpm, the linear speed of stirring is independently 5 m / s to 10 m / s, and the time of stirring is independently 1 min to 10 min;

[0031] The rotating speed of mixing and stirring after the second binder glue is added in step A3 is 30 rpm to 80 rpm; the linear speed of mixing and stirring is 18 m / s to 23 m / s, and the time of mixing and stirring is 60 min to 150 min.

[0032] The application also provides a solid-state battery comprising the silver-carbon negative electrode sheet.

[0033] Preferably, the solid-state battery further comprises a positive electrode sheet; the positive electrode sheet comprises a positive electrode active layer; the positive electrode active layer comprises a positive electrode active material; the positive electrode active material is selected from lithium iron phosphate or ternary material.

[0034] Preferably, the positive active material is selected from lithium iron phosphate; the S0 / S is 0%~25%.

[0035] Preferably, the positive active material is selected from LiNi x Co y Mn 1-x-y O2; 0.33≤x≤0.65, 0.2≤y≤0.33; the S0 / S is 0%~17%.

[0036] Preferably, the positive active material is selected from LiNi x Co y Mn 1-x-y O2; 0.8≤x≤0.95, 0.02≤y≤0.1, and x+y<1; the S0 / S is 0%~10%.

[0037] Preferably, the solid-state battery further comprises a solid-state electrolyte; the solid-state electrolyte is selected from sulfide electrolyte.

[0038] The application also provides a preparation method of the coating slurry, comprising the following steps:

[0039] S1) mixing silver particles, a binder and an additive to obtain a first mixture;

[0040] S2) adding a solvent to the first mixture and stirring to obtain a second mixture; the solid content of the second mixture is 20%~50%;

[0041] S3) adding carbon particles and a solvent to the second mixture in batches in a circulation manner, and mixing until the viscosity of the slurry is 2500~5500 mPa / s and the solid content is 10%~45% to obtain the coating slurry;

[0042] Alternatively, comprising the following steps:

[0043] A1) mixing a binder powder and a solvent to obtain a binder glue, and dividing the binder glue into a first binder glue and a second binder glue;

[0044] A2) mixing and stirring the first binder glue, silver particles, an additive and a solvent to obtain a third mixture; the solid content of the third mixture is 20%~50%;

[0045] A3) adding carbon particles and a solvent to the third mixture in batches in a circulation manner, then adding the second binder glue and mixing and stirring to adjust the viscosity of the slurry to 2500~5500 mPa / s and the solid content to 10%~45% to obtain the coating slurry.

[0046] Compared with the prior art, the application can increase the adhesion sites and space of silver particles on carbon particles on the basis of avoiding the generation of lithium dendrites by controlling the agglomeration degree of silver material in the negative active coating, thereby improving the safety performance and electrical performance of the battery. BRIEF DESCRIPTION OF DRAWINGS

[0047] Figure 1 Figure is a schematic diagram of the diameter of Ag particles in a field emission scanning electron microscope image. DETAILED DESCRIPTION

[0048] The technical solutions in the embodiments of the application will be clearly and completely described below with reference to the embodiments of the application. Obviously, the described embodiments are only part of the embodiments of the application, rather than all the embodiments of the application. Based on the embodiments in the application, all other embodiments obtained by those skilled in the art without creative efforts belong to the protection scope of the application.

[0049] The application provides a silver-carbon negative electrode sheet, which comprises a negative electrode current collector and a negative active coating attached to at least one surface of the negative electrode current collector; the negative active coating comprises silver particles and carbon particles; the area of first particles with a particle diameter greater than or equal to 200 nm in a scanning electron microscope image of the negative active coating at a magnification of 100KX is S0, and the area of the silver-carbon negative electrode sheet in the scanning electron microscope image at a magnification of 100KX is S, S0 / S≤39.8%.

[0050] In the application, the particles with a diameter greater than or equal to 200 nm are defined as first particles (the diameter refers to the maximum distance from a point of a particle to its opposite point), and the first particles are formed by agglomeration of silver particles during the dispersion process in carbon particles, and thus have a relatively large diameter. If the area ratio of the first particles with a particle diameter greater than or equal to 200 nm in a scanning image of the negative active coating at a magnification of 100KX is too large, it indicates that the silver particles are seriously agglomerated, which may cause the generation of lithium dendrites and affect the safety and electrical performance of the battery. Therefore, the area of the first particles with a particle diameter greater than or equal to 200 nm in a scanning electron microscope image of the negative active coating at a magnification of 100KX is S0, the area of the negative active coating is S, and S0 / S≤39.8%. Within this range, the silver and carbon particles are uniformly dispersed, the generation of lithium dendrites can be avoided, and the safety and electrical performance of the battery can be ensured. Specifically, the S is the area of the negative active coating in the scanning electron microscope image; optionally, the S0 / S is 0%, 1%, 2%, 2.5%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 13.6%, 15%, 20%, 25%, 30, 35%, 39.8%, or a range between any two of the above values.

[0051] In a specific embodiment provided in the present application, if the area ratio is too small, the silver particles are uniformly dispersed, indicating that more auxiliary agents (dispersants, binders) are added during the slurry preparation process. These auxiliary agents are electronically insulating, thereby reducing the conductivity of the negative electrode and affecting the cycle performance of the battery. Therefore, the S0 / S is preferably 2.5% to 25%.

[0052] In the present application, the negative current collector is a negative current collector known to those skilled in the art, and there is no special limitation. In the present application, it is preferably copper foil, carbon-coated copper foil, nickel-plated copper foil, nickel-plated copper foil, stainless steel foil, etc. The stainless steel foil is preferably roughened stainless steel foil. In the present application, the negative current collector is more preferably nickel-plated copper foil or roughened stainless steel foil, which has high corrosion resistance.

[0053] At least one surface of the negative current collector is provided with a negative active coating layer; the negative active coating layer comprises silver particles and carbon particles.

[0054] In the present application, the silver particles are preferably nano-silver particles; the D50 of the silver particles is preferably 5 to 90 nm, and more preferably 10 to 80 nm; optionally, the D50 of the silver particles is 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 75 nm, 80 nm, 85 nm, 90 nm, or a range between any two of the above values; the silver particles are preferably one or more of spherical silver particles, flaky silver particles, dendritic silver particles, and cubic silver particles; due to the flaky structure, the contact area between adjacent silver particles is larger, which is beneficial for the transmission of electrical signals, and the resistance after film formation is smaller, having excellent conductivity. The specific surface area of the spherical particles is large, and it is easier to contact lithium, so in the present application, the silver particles are more preferably flaky silver material and / or spherical silver particles; in other embodiments, dendritic silver particles and / or cubic silver particles can also be selected.

[0055] In the present application, the carbon particles are carbon particles known to those skilled in the art, and there is no special limitation. In the present application, they are preferably one or more of carbon black, carbon tubes, and carbon fibers; the average particle size of the carbon particles is preferably 5 to 200 nm. Optionally, the average particle size of the carbon particles is 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, or a range between any two of the above values.

[0056] In a specific embodiment provided in the present application, the average particle size of the carbon particles is preferably 10-100 nm.

[0057] In the present application, the silver particles are dispersed in the carbon material to form the negative active coating layer. If the content of the silver particles in the negative active coating layer is too large, the silver particles cannot be attached to the carbon material, resulting in too high degree of agglomeration. Therefore, the mass of the silver particles is preferably 10%-40% of the mass of the carbon particles. Alternatively, the mass of the silver particles is 10%, 15%, 20%, 25%, 30%, 35%, 40% of the mass of the carbon material, or a range between any two of the above values.

[0058] In a specific embodiment provided in the present application, the mass of the silver particles is preferably 20%-30% of the mass of the carbon particles.

[0059] In a specific embodiment provided in the present application, the S is the area of the silver-carbon negative electrode sheet under a scanning electron microscope image at 100KX magnification. The S is 0.88 μm 2 The S0 is preferably 0.12-0.35 μm 2 , and more preferably 0.14-0.22 μm 2 .

[0060] In a specific embodiment provided in the present application, the test method of the S0 is as follows: using a field emission scanning electron microscope, taking a SEM image at 100KX magnification (100000 times) under a scale of 100 nm, performing area division processing (10x10) on the image, and calculating the length, width and area of each grid according to the scale size, then measuring and calculating the cumulative area S0 of the Ag particle display area, and the area of the electrode sheet under 100KX is S.

[0061] In a specific embodiment provided in the present application, the field emission scanning electron microscope is used to detect the negative electrode sheet after the battery is disassembled. The disassembling step of the battery is as follows: 1) discharging the battery at a discharge rate of 1 / 3C, the discharge voltage is 2.5-4.25 V, the lower limit cutoff voltage is 2.5 V, discharging at a rate of 0.1C in the second cycle, the discharge cutoff voltage is 2.5 V, repeating the 0.1C discharge for 2 cycles until the battery is in an empty state; 2) disassembling the empty battery, selecting the negative electrode sheet area, performing transverse cutting at the coating position, and then taking a picture.

[0062] The area of the first particle in the scanning electron microscope image of the negative electrode active coating is affected by the shape of the silver particle, the particle size of the silver particle and the particle size of the carbon particle. In a specific embodiment provided by the present application, the silver particle is preferably a flaky silver particle; the D50 of the silver particle is preferably 10-80 nm; the average particle size of the carbon particle is preferably 10-100 nm; and the mass of the silver particle is preferably 20%-30% of the mass of the carbon particle.

[0063] In a specific embodiment provided by the present application, the negative electrode active coating further comprises a binder; the binder can be any binder known to those skilled in the art without special limitation, and is preferably polyvinylidene fluoride (PVDF) in the present application; the mass of the binder is preferably 2%-25% of the mass of the negative electrode active coating; optionally, the mass of the binder is 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25% of the mass of the negative electrode active coating, or a range between any two of the above values.

[0064] In a specific embodiment provided by the present application, the molecular weight of the PVDF is preferably 60-220 W; optionally, the molecular weight of the PVDF is 60 W, 65 W, 70 W, 75 W, 80 W, 85 W, 90 W, 95 W, 100 W, 110 W, 120 W, 130 W, 140 W, 150 W, 160 W, 170 W, 180 W, 190 W, 200 W, 210 W, 220 W, or a range between any two of the above values.

[0065] In a specific embodiment provided by the present application, the negative electrode active coating further comprises an auxiliary agent; the auxiliary agent can be any auxiliary agent known to those skilled in the art, and is preferably a dispersant, which is beneficial to the dispersion of the silver material; the dispersant preferably comprises, but is not limited to, one or more of sodium dodecyl benzene sulfonate, sodium dodecyl sulfate, cetyl trimethyl ammonium bromide, polyvinylpyrrolidone (PVP) and polyoxyethylene ether; the mass of the dispersant is preferably 0.2%-5% of the mass of the negative electrode active coating; optionally, the mass of the dispersant is 0.2%, 0.5%, 1%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0% of the mass of the negative electrode active coating, or a range between any two of the above values.

[0066] The present application can control the degree of agglomeration of the silver particles in the negative electrode active coating, increase the adhesion sites and space of the silver particles on the carbon particles on the basis of uniform dispersion of the silver and carbon particles and avoidance of lithium dendrite, and thus improve the safety performance and electrical performance of the battery.

[0067] The application further provides a preparation method of the coating slurry of the negative electrode active coating.

[0068] In the application, the sources of all raw materials are not specially limited and can be commercially available; the types and particle sizes of the silver particles and the carbon particles are the same as described above and will not be repeated here.

[0069] The silver particles, the binder powder and the additives are mixed to obtain a first mixture; the binder and the additives are the same as described above and will not be repeated here; the rotation speed of the mixing is preferably 10-40 rpm; optionally, the rotation speed of the mixing is 10 rpm, 20 rpm, 30 rpm, 40 rpm or a range between any two of the above values; the linear speed of the mixing is preferably 5-10 m / s; the mixing time is preferably 5-20 min, more preferably 5-15 min, and even more preferably 10 min; the mixing is preferably carried out in a double planetary stirring tank, a double screw stirring tank, a kneader, a planetary centrifugal mixer or a ball mill.

[0070] The solvent is a solvent commonly used in the preparation of negative electrode coating slurry by those skilled in the art and is not specially limited, and N-methyl pyrrolidone (NMP) is preferred in the application.

[0071] In a specific embodiment provided by the application, the solvent is preferably added in batches, and more preferably, the solvent is added in the following way: a part of the solvent is added to the first mixture to obtain a solid content of 30-60% for first mixing and stirring, and then the solvent is continuously added to obtain a solid content of 20-50% for second mixing and stirring, to obtain the second mixture.

[0072] In one specific embodiment provided by the present application, part of the solvent is added to the first mixture to a solid content of 30% to 60%, and after mixing and stirring, the state is dough-like or slightly thin; optionally, part of the solvent is added to a solid content of 30%, 40%, 50%, 60%, or a range between any two of the above values; the rotation speed of the first mixing and stirring is preferably 30 to 80 rpm; optionally, the rotation speed of the first mixing and stirring is 30 rpm, 40 rpm, 50 rpm, 60 rpm, 70 rpm, 80 rpm, or a range between any two of the above values; the time of the first mixing and stirring is preferably 30 to 60 min; optionally, the time of the first mixing and stirring is 30 min, 40 min, 50 min, 60 min, or a range between any two of the above values.

[0073] In one specific embodiment provided by the present application, part of the solvent is added to the first mixture to a solid content of 30% to 60%, and after mixing and stirring, the state is dough-like or slightly thin; optionally, part of the solvent is added to a solid content of 30%, 40%, 50%, 60%, or a range between any two of the above values; the rotation speed of the first mixing and stirring is preferably 30 to 80 rpm; optionally, the rotation speed of the first mixing and stirring is 30 rpm, 40 rpm, 50 rpm, 60 rpm, 70 rpm, 80 rpm, or a range between any two of the above values; the time of the first mixing and stirring is preferably 30 to 60 min; optionally, the time of the first mixing and stirring is 30 min, 40 min, 50 min, 60 min, or a range between any two of the above values.

[0074] The carbon particles and the solvent are added in batches in cycles in the second mixture, which means that the carbon particles and the solvent are added in batches in cycles, and each batch of carbon particles and solvent is added, and the next batch of the step is recycled; the number of cycles of the batch addition is greater than or equal to 3; the amount of carbon particles and solvent added in each batch can be the same or different, and there is no special limitation; the stirring speed of each batch of carbon particles and solvent after being added is independently preferably 10-40 rpm; optionally, the stirring speed of each batch of carbon particles and solvent after being added is independently 10 rpm, 20 rpm, 30 rpm, 40 rpm, or a range between any two of the above values; the linear velocity of each batch of carbon particles and solvent after being added is independently preferably 5-10 m / s; the stirring time of each batch of carbon particles and solvent after being added is independently preferably 1-10 min, more preferably 3-8 min, and more preferably 5 min. The stirring speed of the last batch of carbon particles and solvent added in the cycle of batch addition of the carbon particles and the solvent is preferably 30-80 rpm; optionally, the stirring speed is 30 rpm, 40 rpm, 50 rpm, 60 rpm, 70 rpm, 80 rpm, or a range between any two of the above values; the linear velocity of the mixing is preferably 18-23 m / s; optionally, the linear velocity of the mixing is preferably 18 m / s, 19 m / s, 20 m / s, 21 m / s, 22 m / s, 23 m / s, or a range between any two of the above values; the mixing time is preferably 60-150 min; optionally, the mixing time is 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, 130 min, 140 min, 150 min, or a range between any two of the above values;

[0075] The viscosity of the slurry is adjusted to 2500-5500 mPa / s, and the solid content is adjusted to 10%-45% to obtain a coating slurry; in the present application, the viscosity of the slurry can be adjusted by adding a solvent; optionally, the viscosity of the coating slurry is 2500 mPa / s, 3000 mPa / s, 3500 mPa / s, 4000 mPa / s, 4500 mPa / s, 5000 mPa / s, 5500 mPa / s, or a range between any two of the above values; optionally, the solid content of the coating slurry is 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, or a range between any two of the above values.

[0076] In a specific embodiment provided by the present application, the viscosity is tested using an LVDV-1T viscometer, and the test conditions are a circulating water area temperature of 28±0.5℃, a sample of 10 mL, a rotor of 27#, and a rotation speed of 30 rpm.

[0077] The application further provides another preparation method of the coating slurry, comprising the following steps: A1) mixing a binder powder with a solvent to obtain a binder glue solution, and dividing the binder glue solution into a first binder glue solution and a second binder glue solution; A2) mixing and stirring the first binder glue solution, silver particles, an additive and a solvent to obtain a third mixture; the solid content of the third mixture is 20-50%; A3) adding carbon particles and a solvent into the third mixture in batches in circulation, and then adding the second binder glue solution to mix and stir, so that the viscosity of the slurry is adjusted to 2500-5500 mPa / s, and the solid content is 10-45%, to obtain the coating slurry.

[0078] In the application, the sources of all raw materials are not specially limited, and can be commercially available; the types and particle sizes of the silver particles and the carbon particles are the same as described above, and will not be repeated here.

[0079] The binder powder is mixed with a solvent to obtain a binder glue solution, and the binder glue solution is divided into a first binder glue solution and a second binder glue solution; the solvent can be any solvent commonly used in the preparation of negative electrode coating slurries, and is not specially limited, and N-methyl pyrrolidone (NMP) is preferred in the application; the mass concentration of the binder in the binder glue solution is preferably 5-20%, more preferably 5-15%, more preferably 5-10%, and most preferably 8%.

[0080] The first binder glue solution, silver particles, an additive and a solvent are mixed and stirred to obtain a third mixture; the mixing and stirring are preferably carried out in a double-planetary stirring tank, a double-screw stirring tank, a kneader, a planetary centrifugal mixer or a ball mill; the solvent can be any solvent commonly used in the preparation of negative electrode coating slurries, and is not specially limited, and N-methyl pyrrolidone (NMP) is preferred in the application; in the application, the first binder glue solution, silver material and additive are first mixed to control the solid content to be 30-60% under a first preset condition, and then the solvent is added to the solid content to be 20-50% under a second preset condition, to obtain the third mixture.

[0081] In a specific embodiment provided by the application, the first binder glue solution is preferably added in batches in this step, and silver particles and an additive are added in part of the first binder glue solution, and then the remaining first binder glue solution is added.

[0082] In one specific embodiment provided by the present application, the first adhesive glue solution, silver particles and the auxiliary agent are mixed and stirred under the first preset condition to control the solid content to be 30% to 60%, and after the mixing and stirring, the state is dough-like or slightly thin. Optionally, the solid content is controlled to be 30%, 40%, 50%, 60% or a range between any two of the above values. The stirring speed under the first preset condition is preferably 30 to 80 rpm. Optionally, the stirring speed under the first preset condition is 30 rpm, 40 rpm, 50 rpm, 60 rpm, 70 rpm, 80 rpm or a range between any two of the above values. The mixing and stirring time under the first preset condition is preferably 30 to 60 min. Optionally, the mixing and stirring time under the first preset condition is 30 min, 40 min, 50 min, 60 min or a range between any two of the above values.

[0083] In one specific embodiment provided by the present application, then the solvent is added to control the solid content to be 20% to 50% and mixed and stirred under the second preset condition to obtain a third mixture. Optionally, the solvent is added to control the solid content to be 20%, 30%, 40%, 50% or a range between any two of the above values. The stirring speed under the second preset condition is preferably 30 to 80 rpm. Optionally, the stirring speed under the second preset condition is 30 rpm, 40 rpm, 50 rpm, 60 rpm, 70 rpm, 80 rpm or a range between any two of the above values. The linear speed under the second preset condition is preferably 18 to 23 m / s. The mixing and stirring time under the second preset condition is preferably 30 to 60 min. Optionally, the mixing and stirring time under the second preset condition is 30 min, 40 min, 50 min, 60 min or a range between any two of the above values.

[0084] The carbon particles and the solvent are added in batches in cycles in the third mixture. The meaning of adding in batches in cycles is that the carbon particles and the solvent are added in batches in sequence. Each batch adds part of the carbon particles and part of the solvent, and the next batch repeats the step. The number of cycles of adding in batches is greater than or equal to 3. The amount of carbon particles and solvent added in each batch can be the same or different, and there is no special limitation. The stirring speed after adding each batch of carbon particles and solvent is independently preferably 10 to 40 rpm. Optionally, the stirring speed after adding each batch of carbon material and solvent is independently 10 rpm, 20 rpm, 30 rpm, 40 rpm or a range between any two of the above values. The linear speed after stirring after adding each batch of carbon particles and solvent is independently preferably 5 to 10 m / s. The stirring time after adding each batch of carbon particles and solvent is independently preferably 1 to 10 min, more preferably 3 to 8 min, and more preferably 5 min.

[0085] After the carbon particles and the solvent are added in batches in cycles, a second binder glue solution is added and mixed and stirred, the viscosity of the slurry is adjusted to 2500-5500 mPa / s, and the solid content is 10%-45%, to obtain a coating slurry; the rotation speed of the mixing and stirring is preferably 30-80 rpm; optionally, the rotation speed of the mixing and stirring is 30 rpm, 40 rpm, 50 rpm, 60 rpm, 70 rpm, 80 rpm, or a range between any two of the above values; the linear speed of the mixing and stirring is preferably 18-23 m / s; optionally, the linear speed of the mixing and stirring is preferably 18 m / s, 19 m / s, 20 m / s, 21 m / s, 22 m / s, 23 m / s, or a range between any two of the above values; the time of the mixing and stirring is preferably 60-150 min; optionally, the time of the mixing and stirring is 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, 130 min, 140 min, 150 min, or a range between any two of the above values; in the present application, the solvent can be added as needed to adjust the viscosity of the slurry; optionally, the viscosity of the coating slurry is 2500 mPa / s, 3000 mPa / s, 3500 mPa / s, 4000 mPa / s, 4500 mPa / s, 5000 mPa / s, 5500 mPa / s, or a range between any two of the above values; optionally, the solid content of the coating slurry is 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, or a range between any two of the above values.

[0086] The present application also provides a preparation method of the above silver-carbon negative electrode sheet, comprising the following steps: S1) mixing silver particles, a binder, and an additive to obtain a first mixture; S2) adding a solvent to the first mixture and mixing and stirring to obtain a second mixture; the solid content of the second mixture is 20%-50%; S3) adding carbon particles and a solvent in batches in cycles in the second mixture, mixing until the viscosity of the slurry is 2500-5500 mPa / s, and the solid content is 10%-45%, to obtain a coating slurry; S4) transferring the coating slurry to the surface of a current collector and drying to obtain a silver-carbon negative electrode sheet.

[0087] The preparation method of the coating slurry is the same as described above, and will not be repeated here.

[0088] The coating slurry is transferred to the surface of a current collector and dried to obtain a silver-carbon negative electrode sheet; the transfer method is a method known to those skilled in the art and is not particularly limited, including but not limited to using a transfer coater, an extrusion coater, and a gravure coater for coating.

[0089] After drying, preferably, rolling, cutting are also carried out to obtain the silver-carbon negative electrode sheet.

[0090] The application further provides another preparation method of the above silver-carbon negative electrode sheet, comprising the following steps: A1) mixing binder powder with solvent to obtain binder glue, and dividing the binder glue into first binder glue and second binder glue; A2) mixing and stirring the first binder glue, silver particles, additives and solvent to obtain a third mixture; the solid content of the third mixture is 20%-50%; A3) adding carbon particles and solvent into the third mixture in batches in circulation, and then adding the second binder glue to mix and stir, so as to adjust the viscosity of the slurry to 2500-5500 mPa / s and the solid content to 10%-45%, thereby obtaining coating slurry; A4) transferring the coating slurry to the surface of the current collector, drying to obtain the silver-carbon negative electrode sheet.

[0091] The preparation method of the coating slurry is the same as described above, and will not be repeated here.

[0092] The coating slurry is transferred to the surface of the current collector, and dried to obtain the silver-carbon negative electrode sheet; the transferring method is a method known to those skilled in the art, and is not particularly limited, including but not limited to using a transfer coater, an extrusion coater, a gravure coater for coating.

[0093] After drying, preferably, rolling, cutting are also carried out to obtain the silver-carbon negative electrode sheet.

[0094] The application further provides a solid-state battery comprising the above silver-carbon negative electrode sheet.

[0095] In a specific embodiment provided by the application, the solid-state battery further comprises a positive electrode sheet; the positive electrode sheet comprises a positive electrode active layer; the positive electrode active layer comprises a positive electrode active material; the positive electrode active material is a positive electrode active material of a solid-state battery known to those skilled in the art, and is not particularly limited, and preferably lithium iron phosphate (LiFePO4) or ternary material (LiNi x Co y Mn 1-x-y O2).

[0096] In the application, the types of positive electrode active materials also have different requirements for negative electrode sheets.

[0097] In a specific embodiment provided by the application, the positive electrode active material is lithium iron phosphate; the energy density of lithium iron phosphate material is low, the lithium ion transmission is relatively slow, the negative electrode interface lithium ion flux is small, and lithium dendrites are not easy to deposit on the negative electrode sheet, so the uniformity of dispersion of silver particles in the negative electrode sheet is not high; at this time, the S0 / S is preferably 0%-25%.

[0098] In a specific embodiment provided by the present application, the positive active material is LiNi x Co y Mn 1-x-y O2; 0.33≤x≤0.65, 0.2≤y≤0.33; the energy density of the ternary nickel system is higher, and the lithium ion transmission is faster, resulting in an increase in the lithium ion flux of the negative electrode interface, and an increase in the risk of lithium dendrite deposition on the negative electrode sheet, so the silver particles in the negative electrode sheet need to be uniformly dispersed; at this time, the S0 / S is preferably 0% to 17%.

[0099] In a specific embodiment provided by the present application, the positive active material is LiNi x Co y Mn 1-x-y O2; 0.8≤x≤0.95, 0.02≤y≤0.1, and x+y<1; the energy density of the ternary nickel system is the highest, and the lithium ion transmission is the fastest, resulting in an excessively high lithium ion flux of the negative electrode interface, and an easy deposition of lithium dendrite on the negative electrode sheet, so the silver particles in the negative electrode sheet need to be more uniformly dispersed; at this time, the S0 / S is preferably 0% to 10%.

[0100] In one embodiment, the positive active layer further comprises a positive electrode binder, a positive electrode conductive agent and an electrolyte. The positive electrode binder includes, but is not limited to, one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA) and polyacrylonitrile (PAN). The mass of the positive electrode binder is preferably 0.01% to 5% of the mass of the positive active layer. Alternatively, the mass of the positive electrode binder is 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0% or a range between any two of the above values of the mass of the positive active layer. The positive electrode conductive agent includes, but is not limited to, one or more of conductive carbon black, carbon nanotubes, graphene and carbon fiber materials. The mass of the positive electrode conductive agent is preferably 0.01% to 20% of the mass of the positive active layer. Alternatively, the mass of the positive electrode conductive agent is 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 8%, 10%, 12%, 15%, 18%, 20% or a range between any two of the above values of the mass of the positive active layer. The electrolyte is a solid-state electrolyte known to those skilled in the art, including, but not limited to, one or more of a polymer solid-state electrolyte, an oxide solid-state electrolyte and a sulfide solid-state electrolyte. The mass of the electrolyte is preferably 0.01% to 5% of the mass of the positive active layer. Alternatively, the mass of the electrolyte is 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0% or a range between any two of the above values of the mass of the positive active layer.

[0101] In one embodiment, the positive electrode sheet further comprises a positive electrode current collector. The positive active layer is disposed on at least one surface of the positive electrode current collector. The positive electrode current collector includes, but is not limited to, an aluminum foil, a carbon-coated aluminum foil and the like.

[0102] In a specific embodiment provided in the present application, the solid-state battery further comprises a solid-state electrolyte; the solid-state electrolyte can be any solid-state electrolyte known to those skilled in the art, and there is no special limitation, and in the present application, one or more of a polymer solid-state electrolyte, an oxide solid-state electrolyte, and a sulfide solid-state electrolyte are preferred; the polymer solid-state electrolyte includes, but is not limited to, lithium lanthanum zirconium oxide (LLZO), lithium aluminum titanium phosphate (LATP), etc.; the oxide solid-state electrolyte includes, but is not limited to, polyethylene oxide (PEO), polyethylene glycol methyl ether methacrylate (PEGMA), etc.; the sulfide solid-state electrolyte includes, but is not limited to, lithium phosphorus sulfur chloride (LPSC), lithium germanium phosphorus sulfide (LGPS), etc.; the composite solid-state electrolyte includes, but is not limited to, polyethylene oxide-lithium lanthanum zirconium oxide (PEO-LLZO), polyvinylidene fluoride-lithium aluminum titanium phosphate (PVDF-LATP), etc.; the thickness of the solid-state electrolyte is preferably 10-60 μm; optionally, the thickness of the solid-state electrolyte is 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, or a range between any two of the above values.

[0103] In the present application, the solid-state battery is prepared according to a method known to those skilled in the art, specifically: the positive electrode sheet, the negative electrode sheet, and the solid-state electrolyte are sliced, laminated, isostatic pressed, welded, etc. according to the design requirements, and finally packaged in a shell.

[0104] In order to further illustrate the present application, the preparation method of the coating slurry, the silver-carbon negative electrode sheet and the preparation method thereof, and the solid-state battery provided in the present application are described in detail below; the molecular weight of PVDF used in the examples and comparative examples is about 70 W.

[0105] The reagents used in the following examples are commercially available.

[0106] The viscosity of the examples and comparative examples is tested using an LVDV-1T viscometer, and the test conditions are a circulating water area temperature of 28±0.5℃, a sample of 10 mL, a rotor of 27#, and a rotation speed of 30 rpm.

[0107] Examples 1-25 and Comparative Examples 1-2

[0108] 1) Preparation method of negative electrode slurry

[0109] S1) Mix silver particles, PVDF powder, and PVP to obtain a first mixture; the amount of PVDF powder is 9% of the solid mass in the negative electrode slurry; the amount of PVP is 3% of the solid mass in the negative electrode slurry; the specific conditions are shown in Table 1;

[0110] S2) adding NMP into the first mixture and stirring to obtain a second mixture; the solid content of the second mixture is 20% to 50%, and the specific conditions are shown in Table 1;

[0111] S3) adding carbon particles (40 nm in size) and NMP into the second mixture in batches and mixing to adjust the viscosity of the slurry to 2500 to 5500 mPa / s and the solid content to 10% to 45% to obtain a negative electrode slurry, and the specific conditions are shown in Table 2;

[0112] A1) mixing PVDF powder and NMP to obtain an 8% glue solution, and dividing the glue solution into a first binder glue solution and a second binder glue solution; the amount of PVDF powder is 9% of the solid mass in the negative electrode slurry;

[0113] A2) mixing the first binder glue solution, silver particles, PVP and a solvent and stirring to obtain a third mixture; the solid content of the third mixture is 20% to 50%; the amount of PVP is 3% of the solid mass in the slurry; and the specific conditions are shown in Table 3.

[0114] A3) adding carbon particles (40 nm in size) and a solvent into the third mixture in batches, then adding the second binder glue solution and mixing to adjust the viscosity of the slurry to 2500 to 5500 mPa / s and the solid content to 10% to 45%, and the specific conditions are shown in Table 3, to obtain a coating slurry.

[0115] 2) Preparation of a negative electrode sheet

[0116] The negative electrode slurry is coated on a current collector, and the current collector is selected as a copper foil, the coating thickness is 30 μm, a double-sided coated electrode sheet is obtained, and then rolling (the compaction density is 1.4 g / m 3 , cutting to obtain a negative electrode sheet.

[0117] 3) Preparation of a positive electrode sheet: 9 series NCM 81%, VGCF 2%, LPSC 15%, PTFE 2%, mixed uniformly according to a certain order and rotation speed and temperature control to prepare a compounded positive electrode dry powder; through a dry film forming device, an electrode sheet is prepared on the surface of a current collector aluminum foil to obtain a double-sided coated electrode sheet, and the compaction density is 3.3 g / m 3 .

[0118] 4) The solid-state electrolyte is sulfide LPSC, and the film thickness is 45 μm.

[0119] 5) Preparation of solid-state battery: the prepared positive electrode sheet, negative electrode sheet, and electrolyte layer are cut, stacked, hot-pressed, warm isostatic pressed, tab welded, packaged, formed, and finally packaged in a shell. The warm isostatic pressing is as follows: the bare cell is placed in a sealed bag into a specific mold, then placed in a sealed container filled with liquid, and then pressed tightly at a temperature of 80°C, a pressure of 590 MPa, and a time of 15 min. The formation and constant volume are as follows: the packaged battery is charged to 4.25V at a certain current, and then discharged to 2.5V at a certain current.

[0120] The particle diameter is greater than or equal to 200 nm (the maximum distance between a certain point of the particle and its opposite, such as the distance between the two ends of the 1 distance as the diameter). Figure 1 The Ag particle area S0 test method is as follows: the battery is disassembled using a Cessna Gemini field emission scanning electron microscope 300, and SEM is taken at 100KX under a scale of 100 nm. The picture is regionally divided (10x10), and the length, width, and area of each grid are calculated according to the scale size. Then the cumulative area S0 of the Ag particle display area is measured and metered, and the area of the electrode sheet under 100KX is S. The results are shown in Table 1.

[0121] The specific steps for disassembling the battery are as follows: 1) the battery is discharged at a discharge rate of 1 / 3C, and the discharge voltage is 2.5-4.25V, the lower limit cutoff voltage is 2.5V, the second circle is discharged at a rate of 0.1C, the discharge cutoff voltage is 2.5V, and the 0.1C discharge is repeated for 2 circles until the battery is in an empty state; 2) the empty battery is disassembled, the negative electrode sheet area is selected, and the coating position is cut horizontally, and then photographed.

[0122] The electrical performance evaluation index (cycle capacity retention rate) test method is as follows:

[0123] The lithium ion batteries prepared in the examples and the comparative examples are subjected to cycle tests at 45°C according to the following procedures: 1) constant current charging to 4.25V at a rate of 1C, and constant voltage charging to a current of 0.05C; 2) standing for 20 minutes; 3) discharging to 2.5V at a rate of 3C; 4) standing for 20 minutes, and repeating steps 1) to 4) to perform cycle tests, and the cycle is repeated for 20 weeks. The results are shown in Tables 2 and 4.

[0124] Table 1 Preparation conditions of the negative electrode slurry in Examples 1-17 and Comparative Example 1

[0125]

[0126] Table 2 Preparation conditions of the negative electrode slurry and performance test results in Examples 1-17 and Comparative Example 1

[0127]

[0128]

[0129] Table 3 Preparation conditions of negative electrode slurry in Examples 18-25 and Comparative Example 2

[0130]

[0131] Table 4 Performance test results of Examples 18-25 and Comparative Example 2

[0132]

[0133] As can be seen from Table 2 and Table 4, the negative active coating has higher cycle stability when the area of silver material particles with a particle diameter of 200 nm or more in the negative active coating is within the range of the present application.

[0134] Comparative Example 3

[0135] Preparation method of negative electrode slurry:

[0136] The Ag powder (22%), carbon black (66%), PVDF powder (9%), and PVP (3%) were mixed at a rotation speed of 35 rpm, a linear speed of 10 m / s, and for a mixing time of 50 min. NMP was added to adjust the solid content to 45.6%, and the mixed slurry was stirred at a rotation speed of 60 rpm for a time of 60 min. NMP was added to adjust the solid content to 41.5%, and the mixed slurry was stirred at a rotation speed of 60 rpm for a time of 120 min and a linear speed of 20 m / s to obtain the negative electrode slurry.

[0137] The rest was the same as in the example, and the capacity retention rate obtained by testing was 92.4%.

[0138] Finally, it should be noted that the above examples are only used to illustrate the technical solutions of the present application and not to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solutions of the present application.

Claims

1. A silver-carbon negative electrode sheet, characterized by, The silver-carbon negative electrode sheet comprises a negative electrode current collector and a negative electrode active coating attached to at least one surface of the negative electrode current collector; the negative electrode active coating comprises silver particles and carbon particles; in a scanning electron microscope image at a magnification of 100KX, the area of the first particles with a particle diameter greater than or equal to 200 nm is S0, and the area of the silver-carbon negative electrode sheet in the scanning electron microscope image at a magnification of 100KX is S, and S0 / S≤39.8%.

2. The silver-carbon negative electrode sheet according to claim 1, characterized by, The S0 / S is 2.5% to 25%.

3. The silver-carbon negative electrode sheet according to claim 1, characterized by, S0 is 0.022 to 0.35 μm 2 .

4. The silver-carbon negative electrode sheet according to claim 1, characterized by, The number of the first particles under the S area is 1 to 5; And / or, the maximum diameter of the first particles is less than or equal to 500 nm.

5. The silver-carbon negative electrode sheet according to claim 1, characterized by, The silver particles are selected from one or more of spherical silver particles, flaky silver particles, dendritic silver particles and cubic silver particles; And / or, the carbon particles are selected from one or more of carbon black, carbon tubes and carbon fibers; And / or, the mass of the silver particles is 10% to 40% of the mass of the carbon particles; And / or, the negative electrode current collector is selected from a copper foil, a carbon-coated copper foil, a nickel-plated copper foil or a stainless steel foil.

6. A method for producing the silver-carbon negative electrode sheet according to any one of claims 1 to 5, characterized by, The method comprises the following steps: S1) mixing silver particles, binder powder and an additive to obtain a first mixture; S2) adding a solvent to the first mixture and mixing to obtain a second mixture; the solid content of the second mixture is 20% to 50%; S3) adding carbon particles and a solvent to the second mixture in cycles in batches to adjust the viscosity of the slurry to 2500 to 5500 mPa / s and the solid content to 10% to 45% to obtain a coating slurry; S4) transferring the coating slurry to the surface of the current collector and drying to obtain a silver-carbon negative electrode sheet; Alternatively, the method comprises the following steps: A1) mixing a binder powder and a solvent to obtain a binder glue solution, and dividing the binder glue solution into a first binder glue solution and a second binder glue solution; A2) mixing the first binder glue solution, silver particles, an additive and a solvent to obtain a third mixture; the solid content of the third mixture is 20% to 50%; A3) adding carbon particles and a solvent to the third mixture in cycles in batches, then adding the second binder glue solution and mixing to adjust the viscosity of the slurry to 2500 to 5500 mPa / s and the solid content to 10% to 45% to obtain a coating slurry; A4) transferring the coating slurry to the surface of the current collector and drying to obtain a silver-carbon negative electrode sheet.

7. The production method according to claim 6, wherein The rotation speed of the mixing in step S1) is 10 to 40 rpm; the linear speed of the mixing is 5 to 10 m / s; and the mixing time is 5 to 20 min; And / or, the solvent is added in batches in step S2), specifically: adding part of the solvent to the first mixture to a solid content of 30% to 60% for first-time mixing and stirring, and continuously adding the solvent to a solid content of 20% to 50% for second-time mixing and stirring to obtain the second mixture; the rotation speed of the first-time mixing and stirring and the rotation speed of the second-time mixing and stirring are each independently 30 to 80 rpm; and the time of the first-time mixing and stirring and the time of the second-time mixing and stirring are each independently 30 to 60 min. The first binder solution, silver particles and additives are mixed in step A2) to control the solid content to 30-60% under first preset conditions, then solvent is added to control the solid content to 20-50% under second preset conditions, and a third mixture is obtained; the stirring speed under the first preset conditions and the stirring speed under the second preset conditions are each independently 30-80 rpm; the stirring time under the first preset conditions and the stirring time under the second preset conditions are each independently 30-60 min.

8. The preparation method according to claim 6, characterized in that, The number of times of cyclic batch addition in step S3) is greater than or equal to 3; the stirring speed after each batch of carbon particles and solvent is added is each independently 10-40 rpm, the linear speed of stirring is each independently 5-10 m / s, and the stirring time is each independently 1-10 min; The stirring speed after the last batch of carbon particles and solvent is added in step S3) is 30-80 rpm; the linear speed of mixing is 18-23 m / s, and the mixing time is 60-150 min; The number of times of cyclic batch addition in step A3) is greater than or equal to 3; the stirring speed after each batch of carbon particles and solvent is added is each independently 10-40 rpm, the linear speed of stirring is each independently 5-10 m / s, and the stirring time is each independently 1-10 min; The stirring speed after the second binder solution is added in step A3) is 30-80 rpm; the linear speed of mixing is 18-23 m / s, and the mixing time is 60-150 min.

9. A solid state battery, characterized by The silver-carbon negative electrode sheet of any one of claims 1-5 or prepared by the method of any one of claims 6-8.

10. The solid-state battery of claim 9, wherein, The solid-state battery further comprises a positive electrode sheet; the positive electrode sheet comprises a positive electrode active layer; the positive electrode active layer comprises a positive electrode active material; the positive electrode active material is selected from lithium iron phosphate or a ternary material.

11. The solid-state battery of claim 10, wherein, The positive electrode active material is selected from lithium iron phosphate; the S0 / S is 0-25%.

12. The solid-state battery of claim 10, wherein, The positive active material is selected from LiNi x Co y Mn 1-x-y O2; 0.33≤x≤0.65, 0.2≤y≤0.33; the S0 / S is 0%~17%.

13. The solid-state battery of claim 10, wherein, The positive active material is selected from LiNi x Co y Mn 1-x-y O2; 0.8≤x≤0.95, 0.02≤y≤0.1, and x+y<1; the S0 / S is 0%~10%.

14. The solid-state battery according to any one of claims 10 to 13, characterized in that, The solid-state battery further comprises a solid-state electrolyte; the solid-state electrolyte is selected from a sulfide electrolyte.

15. A method of preparing a coating slurry, characterized by, The following steps are included: S1) mixing silver particles, a binder and additives to obtain a first mixture; S2) adding solvent to the first mixture and mixing to obtain a second mixture; the solid content of the second mixture is 20-50%; S3) cyclically adding carbon particles and solvent in batches to the second mixture, and mixing until the viscosity of the slurry is 2500-5500 mPa / s and the solid content is 10-45% to obtain a coating slurry; Alternatively, the following steps are included: A1) mixing a binder powder and solvent to obtain a binder solution, and dividing the binder solution into a first binder solution and a second binder solution; A2) mixing the first binder solution, silver particles, additives and solvent to obtain a third mixture; the solid content of the third mixture is 20-50%; A3) cyclically adding carbon particles and solvent in batches to the third mixture, and mixing until the viscosity of the slurry is 2500-5500 mPa / s and the solid content is 10-45% to obtain a coating slurry; A3) in the third mixture, the carbon particles and solvent are added in batches in circulation, then the second binder glue solution is added and mixed and stirred, the slurry viscosity is adjusted to 2500-5500 mPa / s, the solid content is 10%-45%, and a coating slurry is obtained.

Citation Information

Patent Citations

  • Sodium-ion battery, sodium-ion battery positive electrode slurry and preparation method of sodium-ion battery positive electrode slurry

    CN117039125A

  • Preparation method of negative current collector of negative-electrode-free lithium metal battery

    CN118039922A

  • Preparation method of positive electrode slurry and lithium ion battery

    CN118173700A

  • Lithium iron phosphate battery positive electrode slurry and preparation method thereof

    CN118198246A

  • Lithium battery silicon-containing negative electrode homogenizing process and negative electrode plate

    CN118315525A

Cited By

  • Composite silver-carbon material with three-dimensional conductive-lithium-conductive network, preparation method thereof, negative electrode and battery

    CN122474616A